2019
DOI: 10.3390/ma13010109
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Mechanical Properties of Flax-Epoxy Composite with Carbon Fibre Hybridisation for Lightweight Applications

Abstract: The effect of unidirectional (UD) carbon fibre hybridisation on the tensile properties of flax fibre epoxy composite was investigated. Composites containing different fibre ply orientations were fabricated using vacuum infusion with a symmetrical ply structure of 0/+45/−45/90/90/−45/+45/0. Tensile tests were performed to characterise the tensile performance of plain flax/epoxy, carbon/flax/epoxy, and plain carbon/epoxy composite laminates. The experimental results showed that the carbon/flax fibre hybrid syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Dhakal and Sain [ 22 ] addressed the tensile characteristics of hybrid fibre (carbon and flax)-reinforced polymer laminated composites and also made a comparative study between the carbon/flax/epoxy, plain flax/epoxy and plain carbon/epoxy laminated composites. Megahed et al [ 23 ] explored the optimal design of hybrid carbon/flax/epoxy laminated beam by performing the modal analysis in order to minimize its weight and cost.…”
Section: Introductionmentioning
confidence: 99%
“…Dhakal and Sain [ 22 ] addressed the tensile characteristics of hybrid fibre (carbon and flax)-reinforced polymer laminated composites and also made a comparative study between the carbon/flax/epoxy, plain flax/epoxy and plain carbon/epoxy laminated composites. Megahed et al [ 23 ] explored the optimal design of hybrid carbon/flax/epoxy laminated beam by performing the modal analysis in order to minimize its weight and cost.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that the wet samples do not have as clear holes as those of dry specimens (Figure 10), indicating the increased ductility of water-immersed samples. [25,26]. The SEM images further reveal that the extent of damage increased with the increase of the incident energy level.…”
Section: Influence Of Moisture Absorption On the Impact Resistance Bementioning
confidence: 83%
“…Different failure modes for flax/VE composites are further explained by the Micro-CT scan illustrated in Figure 15, which compliments the observation made via SEM images. From the annotation provided for the SEM images of flax/VE composites, as shown in Figure 13a [25,26]. The SEM images further reveal that the extent of damage increased with the increase of the incident energy level.…”
Section: Visual Observations Of Damage Behaviour In Wet Conditionsmentioning
confidence: 94%
See 2 more Smart Citations